Formant analysis for Kiswahili vowels - Sungita , Y. Y.; Mhamilawa , E. E. (Tanzania Journal of Science, 2021)
Vowels' spectral characteristics in a language have been studied for suitability in speech recognition by using formants analysis technique. Other techniques do mostly require large computer memories for speech processing and analysis. In this paper, the formant analysis for Kiswahili vowels has been presented. The spectrographs for each vowel and their respective average formant frequencies are tabled. The distribution of formants for the vowels modelled in the form of an articulatory model is shown. The results show that there is a big separation of formant frequencies among the Kiswahili vowels that signify the suitability for automatic speech recognition.